Analysis of Effective Nursing Supervision Models to Improve the Quality of Services and Patient Satisfaction: Literature Review - Cucu Sri Rahayu; Dyah Wiji Puspita Sari; Muh. Abdurrouf; Iwan Ardian (Indonesian Journal of Global Health Research, 2025)
Many murder services as an indicator of the quality of health services are one of the determining factors for the image of health service institutions in the eyes of the public. Therefore, there is a need for a management function that can improve health services. Clinical supervision is an effective method in improving health services.Objective: To identify effective surgical supervision models to improve service quality and patient satisfaction.Method: This research uses a literature review design. Journal searches were carried out on the Researchgate, Elseiver, Science, Direct, EBSCO, E-Journal, Proquest E-Journals databases. A total of 10 articles were obtained which were then extracted.Results: Clinical supervision in its implementation must be based on evidence-based nursing practice so that clinical supervision can be implemented effectively. Proctor model supervision is effective clinical supervision because it contains three functions, namely a normative function in efforts to develop professionalism; formative function in efforts to develop skills and knowledge; and restorative function in an effort to provide support.Conclusion: implementing proctor model clinical supervision can improve service quality and patient satisfaction.